The Bounds of Myth : The Logical Path from Action to Knowledge - Esparza, Gustavo,; Bravo, Nassim, (Value Inquiry Book Series ;, 2021)
"This book shed light on the internal shapes of the mythological discourse, showing the way in which myth borders religion, science, literature, theology, i.e., other forms of rationality. The contributing authors of the volume claim that myth is a valid form of thought and that the former evolves within other forms of discourse, even though its composition is independent and even precedes the latter"--